Adaptación de chione subrugosa en sistemas de cultivo controlados camaronera utilizando canasta sumergidas a diferentes densidades - Lojano Cabrera, Carlos Alejandro (2012)
The present research was conducted in the shrimp located in the El Coco Machala belonging to the canton of the province of El Oro, aims to cultivate Chione subrugosa in shrimp ponds using drawers. This culture system is an alternative to shrimp farmers and riverside communities benefit from these techniques to get and keep the species disappears, promoting the conservation of natural resources and good use as well and environmental service. For this reason, in this research has the following objective: 1. Determine the optimal biological response in drawers conical Chione subrugosa. 2. Analyze phytoplankton richness (qualitative and quantitative) of the culture medium as a staple for subrugosa Chione. Planting of the Chione subrugosa be directly covered conical mesh drawers anchovy on top. These will be submerged to 1.5 m deep drawers for holding two mangrove stakes. The number of organisms grown in this investigation will be 360 ​​Chione subrugosa having a booking stock if necessary. It will work with densities of 20, 40 and 60 bodies per drawer subrugosa Chione 40x60x20 centimeters. The biological parameter control is performed from the first day after seeding and every 15 days for 5 months.